DETERMINANTS OF GOLD RETURN IN INDONESIA: EMPIRICAL EVIDENCE OF INFLATION, EXCHANGE RATES, OIL PRICES, CAPITAL MARKET PERFORMANCE, AND WORLD GOLD PRICES - Fikri Budi Aulia; Sutrisno Sutrisno; Zaenal Arifin (Bajang Institute, 2026)
This study aims to analyze the determinants of gold return in Indonesia using the static approach of Ordinary Least Squares (OLS) and the dynamic approach of Vector Autoregression (VAR) equipped with the Impulse Response Function (IRF). The research variables include inflation (INF), USD/IDR (KURS), world oil prices (OIL), capital market performance proxied by JCI (CMP), and world gold prices (XAUUSD). The data used is in the form of monthly data for the period January 2009-December 2025. Domestic gold returns are measured using Antam gold. The findings show the difference in results between static and dynamic models. In the OLS model, inflation has a significant negative effect on gold returns at a significance level of 10%, while other variables are insignificant. In the VAR model with an optimal lag of 2, the exchange rate has a significant positive effect on lag-2 and oil prices have a significant positive effect on lag-1 on gold returns. IRF analysis shows that capital market performance shocks produce strong but relatively brief negative responses, while exchange rate shocks and XAUUSD produce more persistent positive responses. Inflation shows the relatively longest duration of the response before returning to the initial condition. These results indicate a time-lagged transmission and a response mechanism that is not entirely in line with the view of contemporary direct relationships. The implications of the study confirm the importance of considering market dynamics and transmission channels when evaluating gold as a safe haven and inflation hedge